The Importance of Motivation, Discipline, and Work Experience on Work Productivity - Dewi Ariska Manik; Hedwigis Esti Riwayati (Jambura Science of Management, 2022)
This study aimed to examine the impact of motivation, work discipline and work experience on news producer productivity of Rajawali Television. This analysis used independent variables, namely motivation, work discipline, and work experience, whereas the dependent variable was work productivity. The sample of this study was 70 news employee of Rajawali Television. The data collected by distributing online questionnaire and processed by using SPSS version 26. It was analyzed using statistical method of multiple linear regression. The results showed that (1) the work motivation variable had no significant effect on employee productivity, (2) the work discipline variable had a positive and significant effect on the work productivity and (3) the work experience variable had a positive and significant effect on work productivity. The coefficient of determination test resulted in an Adjusted R Square of 62 percent which indicates a strong correlation between the dependent variable, namely work productivity, with the independent variables, namely motivation, work discipline, and work experience. The remaining 38 percent are influenced by other variables aside from this study.